The Andean Regional Electricity Market: Energy Trade Opportunities in the South Cone - Chavez-Orostica, H (Institute of Electrical and Electronics Engineers Inc., 2019)
In 2018, the Andean Community of Nations created The Andean Regional Electricity Market, in order for the countries within the community to trade electricity in a regulated and agreed manner. This work describes the details of the new regulatory framework for energy trade and presents an illustrative example to model the expected electricity flows in various scenarios. © 2019 IEEE.